Tugas dan Kewenangan Vts Batam dalam Pengawasan Lalu Lintas Pelayaran Di Selat Singapura - Adhitia Adhitia; Idham Idham; Fadlan Fadlan (Universitas Batanghari Jambi, 2022)
The government, as well as all of us as rulers, managers and users of the sea, are responsible for regulating the flow of traffic to ensure that maritime activities run smoothly and safely. This requires defining channel and crossing functions, which can be done through the use of navigational hazard labeling and updating of water level conditions. The purpose of this study is to find out how the VTS legal duties and authorities are arranged in the supervision of shipping traffic in the Singapore strait, how the VTS Batam duties and authorities are carried out, and what factors hinder the VTS legal duties and authority in supervising shipping traffic in the strait. Singapore. This study collects primary data through fieldwork using a normative and sociological research approach. To collect primary data, descriptive technique is combined with a normative approach (legal research). For marine activities, some locations must be equipped with a Vessel Traffic Information System (VTS) or Radar Beacons for security and strategic considerations. The decision will be announced by the Minister as soon as all the shipping lane requirements have been met, and will be communicated to the maritime world through the International Maritime Organization (IMO), in accordance with the convention that has adopted the standard for the use of shipping lanes. reporting system of ships at sea to operators on land traffic monitoring. This equipment has a VTIS attached to it, enabling it to detect the ship's name, position, speed and course. This data is then entered into the system and continuously monitored.